The Effects of Neurodevelopmental Therapy on Feeding and Swallowing Activities in Children with Cerebral Palsy - TÜRKDOĞAN, DİLŞAD; ACAR, GÖNÜL; ENVER, NECATİ (SPRINGER, 2022)
This study investigated the effect of the structured Neurodevelopmental Therapy Method-Bobath (NDT-B) approach on the feeding and swallowing activity of patients with cerebral palsy (CP) and feeding difficulties. In addition to feeding and oral motor intervention strategies (OMIS), and nutrition-related caregiver training (NRCT), and the NDT-B, which was structured to increase trunk and postural control, was added to the therapy program. Forty patients with CP, with a mean age of 3.25 +/- 0.927 years, were classified using the Gross Motor Function Classification System, Eating and Drinking Ability Classification System, and Mini-Manual Ability Classification System. The patients were randomly assigned into two groups as OMIS + NRCT (n = 20) and OMIS + NRCT + NDT-B (n = 20). The program was applied for 6 weeks, 2 days/week, for 45 min. The patients were evaluated using the Trunk Impairment Scale, Schedule for Oral Motor Assessment, and the Pediatric Quality of Life Inventory before and after 6 weeks. The trunk control of the OMIS + NRCT + NDT-B group was superior to the other group (P = 0.026). Although there was an improvement in the groups according to the subcategories of SOMA, the OMIS + NRCT + NDT-B group was superior in the trainer cup and puree subcategories of SOMA (P = 0.05). A significant correlation was observed between trunk control and oral motor functions in children with CP, and the eating function of children in the OMIS + NRCT + NDT-B group further improved. NDT-B-based neck and trunk stabilization exercises should be added to the treatment programs.
Keywords: Cerebral palsy; Neck and trunk stabilization; Swallowing; Neurodevelopmental therapy; Oral motor intervention strategies; Dysphagia; QUALITY-OF-LIFE; TRUNK IMPAIRMENT SCALE; FIBEROPTIC ENDOSCOPIC EVALUATION; ORAL-MOTOR DYSFUNCTION; INTEROBSERVER RELIABILITY; DIFFICULTIES; SYSTEM; INTERVENTIONS; VALIDITY; CLASSIFY